Data base of Age, sex and adiposity correlates of physical fitness in Costa Rican police academy cadets - Cervantes-Sanabria, Jorge (2025)
This study had the following objectives: (i) to characterize pre-academy physical fitness, (ii) to analyze differences by age and sex, and (iii) to examine the associations between body fat percentage (BF%) and physical fitness in Costa Rican police cadets. A total of 393 cadets participated (age = 24.98 ± 4.65 years, weight = 72.78 ± 12.39 kg, height = 1.70 ± 0.09 m). Data were stratified into groups of 20-29 and 30-39 years of age and analyzed by sex and BF%. The tests were performed between 1 and 3 weeks during the basic training, evaluating body composition, grip strength, flexibility (S&R), vertical jump (VJ), agility (Illinois test), speed (30 m), as well as anaerobic (300 m) and aerobic (2.4 km) capacity. Physical fitness varied by sex (p < 0.05), except for BMI and S&R. In men, each 1% increase in body fat (%) was associated with a loss of +0.034 s in agility (p = 0.004), +0.025 s in 30 m-sprint (p = 0.000), -0.20 kg, and -0.19 kg in grip strength (p = 0.010; p = 0.021), -0.64 cm in VJ (CMJ, p = 0.000), and -0.36 ml∙kg-1∙min-1 in VO2 max (p = 0.000). In women, it was associated with a loss of agility (+0.089 seconds, p = 0.000), VJ (CMJ = -0.39 cm, p = 0.000), 30 m sprint (+0.046 seconds, p = 0.000), 300 m sprint (+1.02 seconds; p = 0.000) and VO2 max (-0.33 ml∙kg-1∙min-1, p = 0.000). The police cadets showed a suboptimal initial physical condition. Age, sex, and body fat (%) are key factors that affect their performance.